The development of a suitable cabbage tissue culture system for gene transformation studies - Latifah Amin,; Mohd Azib Salleh,; Abdul Karim Abdul Ghani,; Mohd Nazir Basiran, (Universiti Kebangsaan Malaysia, 2006)
Experiments were carried out to establish optimum culture condition and to identify the most responsive hypocotyls segments to regenerate shoots in the presence of slight callus for the local cabbage cultivar, Brassica oleracea L. var capitata subvar. kkcross. Results of the study showed that only the upper segment of the hypocotyls (1 cm and 2 cm from both shoot apex) excised from in vitro seedlings, regenerate shoots while the segment nearest to the apex (1 cm) regenerate both shoots and roots. Optimum regeneration was obtained when the seedlings' age were 3 weeks old as compared to younger or older explants. Types of culture vessels did not exhibit any significant effect on the hypocotyls culture. Multiple shoots with the presence of slight healthy callus (0.5 - 2.0mm diameter) were successfully regenerated at a frequency of 42 and 50% respectively from hypocotyls sections cultured on a basal Murashige and Skoog (MS) medium supplemented with 3-lndole acetic acid (1AA) [1 µg/L (w/v)], kinetin [2 µg/L(w/v)] and casein hydrolysate [500 µg/L(w/ v)] (designated as Ms1 medium) and B5 medium supplemented with adenine sulphate [40 mg/L(w/v)], glutamine (6mM) and 2, 4,5-trichlorophenoxyacetic acid [2,4,5- T (0.1 mg/L( w/v)] (designated as cs23 medium). Clonal propagation from axillary buds was induced on a basal MS medium supplemented with low concentration of kinetin [0.05-0.2mg/L(w/v)]. Plantlets with complete roots were successfully transferred into a mixture of soil and vermiculate (1: 1) and grown into normal mature cabbage plants in the glasshouse.